Mental health crisis in healthcare providers in the COVID-19 pandemic: a cross-sectional facility-based survey. Issue 7 (28th July 2021) - Sung, Chih-Wei; Chen, Chi-Hsin; Fan, Cheng-Yi; Chang, Jia-How; Hung, Chia Chun; Fu, Chia-Ming; Wong, Li Ping; Huang, Edward Pei-Chuan; Lee, Tony Szu-Hsien
Abstract : Objectives: During a pandemic, healthcare providers experience increased mental and physical burden. Burnout can lead to treatment errors, patient mortality, increased suicidal ideation and substance abuse as well as medical malpractice suits among medical staff. This study aimed to investigate the occurrence of burnout, acute stress disorder, anxiety disorder and depressive disorder among healthcare providers at the third month of the COVID-19 pandemic. Design: A cross-sectional facility-based survey. Setting: Hospitals around the country with different levels of care. Participants: A total of 1795 respondents, including 360 men and 1435 women who participated in the survey. Primary outcome measures: Burnout was assessed using the Physician Work Life Study. A score of ≥3 implied burnout. Results: Of the 1795 respondents, 723 (40.3%) reported burnout, and 669 (37.3%) cared for patients with COVID-19. Anxiety levels were mild in 185 (10.3%) respondents, moderate in 209 (11.6%) and severe in 1401 (78.1%). The mean Center for Epidemiologic Studies Depression Scale-10 score was 9.5±6.3, and 817 (45.5%) respondents were classified as having depression. Factors associated with burnout were working in acute and critical care (ACC) divisions (adjusted OR (aOR)=1.84, 95% CI 1.20 to 3.39, p=0.019), caring for patients with COVID-19 (aOR=3.90, 95% CI 1.14 to 13.37, p=0.031) and having depressive disorder (aOR=9.44, 95% CI 7.44 to 11.97, p<0.001). Conclusions: Physicians and nurses are vulnerable to burnout during a pandemic, especially those working in ACC divisions. Anxiety disorder, depressive disorder and care of patients with COVID-19 may be factors that influence the occurrence of burnout among healthcare providers.